Literacy ‘Resettlement Stories’ of South Sudanese Refugees in Australia - Woul, GAK (International Journal of Language and Literary Studies, 2025)
The early years of the twenty-first century were a distinctive period in the history of Australia’s hospitality to refugees from Sudan and South Sudan. Significant numbers of South Sudanese refugees arrived in Australia in the decade 2000–2010. Although these numbers later decreased, commitments were made by the Australian government to provide refugee-sensitive initiatives to settle refugees successfully. This study explores the literacy resettlement experiences of South Sudanese refugees in Australia between 2000 and 2010, examining how diverse literacy practices shaped their resettlement experiences. Highlighting the challenges and opportunities these refugees faced in adapting to a new linguistic and cultural environment, this paper shows that these refugees engaged in a range of informal, non-formal and formal literacy practices—including in Adult Migrant English Program language classes—that were significant for their resettlement journeys. Understanding these refugees’ literacy resettlement experiences can be both empowering and challenging experiences, can provide valuable insights into their integration process.